Ribosome biogenesis and degradation regulate translational capacity during muscle disuse and reloading. Issue 1 (24th November 2020) - Figueiredo, Vandré C.; D'Souza, Randall F.; Van Pelt, Douglas W.; Lawrence, Marcus M.; Zeng, Nina; Markworth, James F.; Poppitt, Sally D.; Miller, Benjamin F.; Mitchell, Cameron J.; McCarthy, John J.; Dupont‐Versteegden, Esther E.; Cameron‐Smith, David
Abstract: Background: Translational capacity (i.e. ribosomal mass) is a key determinant of protein synthesis and has been associated with skeletal muscle hypertrophy. The role of translational capacity in muscle atrophy and regrowth from disuse is largely unknown. Therefore, we investigated the effect of muscle disuse and reloading on translational capacity in middle‐aged men (Study 1) and in rats (Study 2). Methods: In Study 1, 28 male participants (age 50.03 ± 3.54 years) underwent 2 weeks of knee immobilization followed by 2 weeks of ambulatory recovery and a further 2 weeks of resistance training. Muscle biopsies were obtained for measurement of total RNA and pre‐ribosomal (r)RNA expression, and vastus lateralis cross‐sectional area (CSA) was determined via peripheral quantitative computed tomography. In Study 2, male rats underwent hindlimb suspension (HS) for either 24 h (HS 24 h, n = 4) or 7 days (HS 7d, n = 5), HS for 7 days followed by 7 days of reloading (Rel, n = 5) or remained as ambulatory weight bearing (WB, n = 5) controls. Rats received deuterium oxide throughout the study to determine RNA synthesis and degradation, and mTORC1 signalling pathway was assessed. Results: Two weeks of immobilization reduced total RNA concentration (20%) and CSA (4%) in men (both P ≤ 0.05). Ambulatory recovery restored total RNA concentration to baseline levels and partially restored muscle CSA. Total RNA concentration and 47S pre‐rRNA expression increased above basal levels after resistance training ( P ≤ 0.05). In rats, RNA synthesis was 30% lower while degradation was 400% higher in HS 7d in soleus and plantaris muscles compared with WB ( P ≤ 0.05). mTORC1 signalling was lower in HS compared with WB as was 47S pre‐rRNA ( P ≤ 0.05). With reloading, the aforementioned parameters were restored to WB levels while RNA degradation was suppressed ( P ≤ 0.05). Conclusions: Changes in RNA concentration following muscle disuse and reloading were associated with changes in ribosome biogenesis and degradation, indicating that both processes are important determinants of translational capacity. The pre‐clinical data help explain the reduced translational capacity after muscle immobilization in humans and demonstrate that ribosome biogenesis and degradation might be valuable therapeutic targets to maintain muscle mass during disuse.